Improving the Management Accounting System through Strategic Budgeting in an Industrial Enterprise - Simakov, K.; Chernyshova, S. (Економічний вісник Донбасу, 2020)
The article defines the principles of formation, development, implementation and use of management accounting at an industrial enterprise. The scheme of making managerial decisions within the concept of budgeting is given. The necessity of determining the role of budgeting in the system of management accounting of an industrial enterprise is substantiated. The relationship between the budgeting process and the strategic goals of the industrial enterprise with the help of a balanced system of indicators, which provides a comprehensive assessment of the strategic indicators of the enterprise by integrating its strategic goals and tactical capabilities.
The mechanism of transformation of strategic goals of an industrial enterprise to the operational level with the help of components of a balanced system of indicators is presented. It is proved that the use of strategic budgets in the system of management accounting makes it possible to improve the quality of current and strategic planning in the enterprise, to make it an effective element of the management system. У статті визначено принципи формування, розробки, впровадження та використання системи управлінського обліку на промисловому підприємстві. Наведено схему прийняття управлінських рішень у рамках концепції бюджетування. Обґрунтовано необхідність визначення ролі бюджетування в системі управлінського обліку промислового підприємства. Досліджено взаємозв'язок між процесом складання бюджету й стратегічними цілями промислового підприємства за допомогою збалансованої системи показників, яка надає всебічну оцінку стратегічних показників підприємства шляхом інтеграції його стратегічних цілей і тактичних можливостей. Представлено механізм трансформації стратегічних цілей промислового підприємства на операційний рівень за допомогою складових збалансованої системи показників. Доведено, що використання стратегічних бюджетів у системі управлінського обліку дає можливість підвищувати якість поточного й стратегічного планування на підприємстві, робити його ефективним елементом системи управління. В статье определены принципы формирования, разработки, внедрения и использования системы управленческого учета на промышленном предпри-
ятии. Приведена схема принятия управленческих решений в рамках концепции бюджетирования. Обоснована необходимость определения роли бюджетирования в системе управленческого учета промышленного предприятия. Исследована взаимосвязь между процессом составления бюджета и стратегическими целями промышленного предприятия с помощью сбалансированной системы показателей, которая предоставляет всестороннюю оценку стратегических показателей предприятия путем интеграции его стратегических целей и тактических возможностей. Представлен механизм трансформации стратегических целей промышленного предприятия на операционный уровень с помощью составляющих сбалансированной системы показателей. Доказано, что использование стратегических бюджетов в системе управленческого учета дает возможность повышать качество текущего и стратегического планирования на предприятии, делать его эффективным элементом системы управления.